2017
DOI: 10.1093/cvr/cvx197
|View full text |Cite
|
Sign up to set email alerts
|

CD40L controls obesity-associated vascular inflammation, oxidative stress, and endothelial dysfunction in high fat diet-treated and db/db mice

Abstract: CD40L controls obesity-associated vascular inflammation, oxidative stress and endothelial dysfunction in mice and potentially humans. Thus, CD40L represents a therapeutic target in lipid metabolic disorders which is a leading cause in cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 66 publications
3
40
1
Order By: Relevance
“…In these experiments, we observed that pre-incubation of aorta segments with antioxidants improved the vascular relaxation in response to Ach in untreated obese mice but not in aorta segments from lean and obese mice supplemented with CSAT+ ® . Thus, these results clearly denote a higher oxidative status in aorta segments from untreated obese mice compared to both lean and CSAT+ ® -treated animals that compromises endothelial function, as it has been previously reported by other authors [53][54][55].…”
Section: Discussionsupporting
confidence: 87%
“…In these experiments, we observed that pre-incubation of aorta segments with antioxidants improved the vascular relaxation in response to Ach in untreated obese mice but not in aorta segments from lean and obese mice supplemented with CSAT+ ® . Thus, these results clearly denote a higher oxidative status in aorta segments from untreated obese mice compared to both lean and CSAT+ ® -treated animals that compromises endothelial function, as it has been previously reported by other authors [53][54][55].…”
Section: Discussionsupporting
confidence: 87%
“…It is worth noting that a HFD had only a small influence on the CES levels in the plasma of the mice (data not shown), which was consistent with the reported research [37]. At the same time, we found that the levels of inflammatory factors TNF-α, IL-1β, and IL-6 in the liver and the intestine of the HFD mice were significantly higher than those in the control mice, in accordance with the clinical outcomes [38][39][40]. It was suggested that a HFD could inhibit the expression and activity of CES of mice, which was probably caused by the severe inflammation accompanying the HFD.…”
Section: Discussionsupporting
confidence: 91%
“…An HFD appeared to induce a slight upregulation of CES in the plasma [37]. In this case, it is noteworthy that patients with hyperlipidemia tended to be accompanied by an inflammatory response [38][39][40]. Numerous reports have described that the significantly increased secretion of various cytokines under pathological circumstances such as inflammation and infection is accompanied by the significantly decreased hydrolytic metabolism of multiple drugs.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our studies also emphasize the need to identify novel therapies inhibiting T cell activation and their recruitment in cardiovascular diseases. 35,36 In summary, we have identified that miR-214 is an essential regulator of T cell dependent mechanisms of vascular stiffening, fibrosis, and dysfunction in hypertension. It may represent a novel biomarker and a possible target for modulation of perivascular inflammation.…”
Section: Discussionmentioning
confidence: 95%